Implementation of Projector Learning Media in Learning Al-Quran Hadith at Madrasah Ibtidaiyah - Mursal Aziz; Muhammad Hasbie Ashshiddiqi; Ayu Wulandari (South Sulawesi Education Development (SSED), 2024)
The aim of this research is to describe the implementation of projector learning media in Al-Qur'an Hadith learning at Madrasah Ibtidaiyah. The research method used in this research is a qualitative research method carried out at MIS Aek Kuasan, North Sumatra. The results of the research found that the use of projector learning media in learning Al-Qur'an Hadith at Madrasah Ibtidaiyah provides a very positive learning experience for students. The aim of using projector learning media is to improve cognitive abilities by providing stimulation in the form of moving images and sound, as well as conveying messages that influence students' attitudes and emotions so that it is easier to understand the Al-Qur'an Hadith learning material presented by the teacher. The use of projector learning media at Madrasah Ibtidaiyah includes animated videos to make it easier for students to understand the material. The application of the use of projector learning media in learning Al-Qur'an Hadith at Madrasah Ibtidaiyah is divided into four stages, namely: planning stage, preparation stage, implementation stage and evaluation stage. The implementation of this media has a very important role in making the learning atmosphere more interesting and making it easier to achieve the objectives of learning Al-Qur'an Hadith at Madrasah Ibtidaiyah.